Canadian journal of pain Revue canadienne de la douleur. (Taylor & Francis, 2017)
The Canadian Journal of Pain, the official journal of The Canadian Pain Society, is a peer-reviewed, open access journal that publishes original articles from all disciplines involved in the study of pain, including the clinical and basic sciences, epidemiology, and health policy and health systems. The aims of the Journal are to advance the understanding and treatment of pain by providing clinicians, scientists and other health care professionals with an interdisciplinary forum in which to share cutting-edge information about new developments in the field of pain.